Orally Disintegrating Tablet Formulation of Avicennia Fruit Ethanol Extract (Avicennia marina) - Ungsari Rizki Eka Purwanto; Maria Caecilia Nanny Setiawati; Ika Puspitaningrum; Siti Munisih (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2021)
The fruit produced from Avicennia tree (in the form of ethanol extract) has the property of reducing blood glucose levels (oral antidiabetic mellitus) with an effective dose of 10 mg / 50 kg human body weight. Most of the elderly with diabetes mellitus in Indonesia are aged 60-74 years (83.3%) who have a decreased ability to swallow drugs. In addition, antidiabetic drugs are expected to be able to produce fast action, so that it can reduce blood sugar levels immediately. Therefore, the Avicennia fruit ethanol extract formulated in the form of Orally Disintegrating Tablet (ODT). The aim of this study was to determine the effect of Starch 1500 and Crospovidone as a superdisintegrant in either single or combination use in the Avicennia fruit ethanol extract ODT formulation. The ODT was made by direct compression. There were three formulas that was carried out in this study : FI with 10 mg of Starch 1500, FII with 10 mg of Crospovidone and FIII with a combination of superdisintegrant Starch 1500 and Crospovidone (7 mg and 3 mg). In this study it could be conclued that the best compatible superdisintegrant in ODT for Avicennia fruit ethanol extract was Crospovidone, not combination with Starch 1500.